The cavum septi pellucidi in euploid and aneuploid fetuses. (26th July 2013) - Abele, H.; Babiy‐Pachomow, O.; Sonek, J.; Hoopmann, M.; Schaelike, M.; Kagan, K. O.
ABSTRACT Objective To examine whether the cavum septi pellucidi (CSP) is larger in second‐ and third‐trimester fetuses with chromosomal abnormalities than in euploid fetuses. Methods This was a retrospective study utilizing stored two‐dimensional images of second‐ and third‐trimester fetuses between 18 and 40 weeks' gestation from three centers in Germany. The width of the CSP was measured by placing the calipers on the inner portion of its lateral borders. Two operators, both of whom were blinded to the fetal karyotype and to the measurements obtained by the other, measured the CSP width. The normal range in euploid fetuses was computed based on the biparietal diameter (BPD) by applying univariate regression analysis. The CSP width in euploid and aneuploid fetuses was transformed into Z‐scores and compared using Student's t‐test. Univariate regression analysis was used to determine the dependency of Z‐score on head biometry. Results The study population consisted of 406 singleton pregnancies, 267 with euploid fetuses, 81 with trisomy 21, 50 with trisomy 18 and eight with trisomy 13. In the euploid group, the mean CSP width was 4.5 (range, 1.8–7.4) mm. Regression analysis showed a significant dependency of CSP width on BPD (CSP width = 0.658 + (0.064 × BPD), r = 0.781, P < 0.0001; both parameters in mm). The mean CSP width increased from 3.2 to 7.1 mm for BPD values of 40 to 100 mm, respectively. In the groups of fetuses with trisomy 21, 18 and 13, mean CSP width was 5.7 (range, 2.8–10.5), 7.9 (range, 3.5–12.8) and 5.8 (range, 4.0–9.0) mm, respectively. In 42.0% of the fetuses with trisomy 21, CSP width was above the 95th centile. In trisomy 18 and 13, CSP width was above the 95th centile in 92.0% and 37.5% of cases, respectively. Conclusion A large CSP width should prompt a detailed ultrasound examination to further assess the risk for chromosomal abnormalities. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.